Enhancing or restoring the productivity of natural populations of shellfish and other marine invertebrate resources - Caddy, J.F.; Defeo, D. (Roma (Italia), 2003)
Sumario (En)
Ilus.; 270 ref.
Keywords: PECES; POBLACION ANIMAL; RECURSOS PESQUEROS; ECOSISTEMA; HABITAT; METODOS DE CULTIVO; PISCICULTURA; PRODUCTIVIDAD; PRODUCCION PESQUERA; RECURSOS MARINOS